EMPLOYEE PERFORMANCE AT THE GENERAL BUREAU OF THE AUDIT AGENCY OF THE REPUBLIC OF INDONESIA - Guguk Kusbiyantoro (Universitas prof. Dr. Moestopo (Beragama), 2022)
This study aims to determine how big the effect of promotions and mutation on employee performance. The research method used is quantitative descriptive analysis. The population of this study is the General Bureau of the Supreme Audit Agency of the Republic of Indonesia (BPK RI) with a total of 183 employees. The sample research method uses the Slovin Formula with a total of 65 employees who can represent the population. Data analysis was performed using the classic assumption test, hypothesis testing using the t test, simple regression analysis, multiple regression analysis, correlation analysis, coefficient of determination, data processing assisted by the IBM SPSS Statistics 2.3 Software program (Statistical Product and Service Solution). The results of the study show that the regression line equation obtains a constant coefficient value of 39.589, meaning that promotion (X1) and mutation (X2) are equal to zero, the level or level of employee performance (Y) is 39.589. Price coefficient b1 = 0.027, the promotion value (X1) has increased by 1%, the other independent variables are fixed, the level of employee performance (Y) has increased by 2.7%. The coefficient value b2 = 0.336 the mutation value (X2) has increased by 1%, the other independent variables are fixed, the level of employee performance (Y) has increased by 33.6%. These results can be a reference for various government agencies in order to improve employee performance. For this reason, it is necessary to pay attention to promotion within the organization.